Production and Quality Control of Fluorine-18 Labelled Radiopharmaceuticals - IAEA (IAEA-TECDOC., 2021)
Since their clinical use initiation in the 1970's, Fluorine-18 (F-18) radiopharmaceuticals continue to play an important role in nuclear medicine. It is therefore essential to make available broad information on practical production routes and optimal quality control for F-18 tracers, to achieve the best possible products in high quantity and quality for clinical applications while fulfilling all regulatory requirements. This publication describes the chemical and biological properties of F-18 radiopharmaceuticals. This includes aspects relating to F-18 target production and radiofluorination methods, with focus on the applied techniques. The publication presents a disease oriented approach, describing F-18 radiopharmaceuticals, ranging from the physiological/biological aspects to dedicated radiopharmaceutical development approaches and provides readers with clear guidelines and methods for the production of F-18 radiopharmaceuticals.